2006
DOI: 10.1021/jp061154p
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organic Semiconductors Including Chalcogen Atoms in π-Conjugated Skeletons. Tuning of Optical, Redox, and Vibrational Properties by Heavy Atom Conjugation

Abstract: In this work, the interactions between heteroatoms (S, Se, and Te) and conjugated skeletons are analyzed. The study is carried out by using electronic absorption and fluorescence spectroscopies, electrochemistry, vibrational Raman spectroscopy, and theoretical calculations in the framework of DFT and TD-DFT theories. Optical spectra are described in terms of one-electron promotions between orbitals around the energy gap. Electrochemistry, in the framework of the Koopman's approach, is also interpreted. The vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 61 publications
2
17
1
Order By: Relevance
“…Addition of electronegative heteroatoms to the conjugated carbon skeleton has been shown to decrease the band gap by decreasing/increasing the LUMO/ HOMO energy, respectively. 99 Heteroatoms can also inuence the packing mode of the crystal. 94 For organic electrodes, functionalization has been commonly applied to modify the LUMO energy and thereby the redox voltage of the compound.…”
Section: Engineering Of Molecular Crystalsmentioning
confidence: 99%
“…Addition of electronegative heteroatoms to the conjugated carbon skeleton has been shown to decrease the band gap by decreasing/increasing the LUMO/ HOMO energy, respectively. 99 Heteroatoms can also inuence the packing mode of the crystal. 94 For organic electrodes, functionalization has been commonly applied to modify the LUMO energy and thereby the redox voltage of the compound.…”
Section: Engineering Of Molecular Crystalsmentioning
confidence: 99%
“…[83,84] However, this shift is associated not just with the increased mass of the selenium atom, but also with an increase in the delocalisation of the π-electron system due in part to greater coplanarity of the conjugated backbone. [85] Several studies have used Raman spectroscopy to probe the impacts of various atomic substitutions on the properties of conjugated molecules, and have shown that this simple chemical variation has profound effects not just on the force constants of the bonds, but also on the electron density distribution over the molecule, and molecular conformation as well as the molecular packing in the solid state. [84][85][86] One class of atomic substitution that has proven particularly useful for enhancing the semiconducting properties of conjugated molecules is fluorination.…”
Section: Heteroatom Substitution and Fluorinationmentioning
confidence: 99%
“…[85] Several studies have used Raman spectroscopy to probe the impacts of various atomic substitutions on the properties of conjugated molecules, and have shown that this simple chemical variation has profound effects not just on the force constants of the bonds, but also on the electron density distribution over the molecule, and molecular conformation as well as the molecular packing in the solid state. [84][85][86] One class of atomic substitution that has proven particularly useful for enhancing the semiconducting properties of conjugated molecules is fluorination. The replacement of hydrogen atoms with fluorine has a strong electron withdrawing effect from the conjugated part of the molecule, and also modifies the molecular packing.…”
Section: Heteroatom Substitution and Fluorinationmentioning
confidence: 99%
“…Structurally similar to thiophene, two other ve-membered heterocycles in the chalcogenophene family-selenophene and tellurophene, featuring group-16 Se and Te elements, respectively-have attracted considerable interest because (1) Se and Te atoms are larger and have d-orbitals of higher polarizability (relative to S) to induce strong Se/Se and Te/Te attractions, potentially strengthening their interpolymer interactions, [37][38][39][40][41] and (2) as the chalcogen becomes heavier, the p-electrons in selenophene and tellurophene tend to adopt a more quinoidal character with higher coplanarity, giving rise to narrower band gaps and bathochromic shis in their absorption. [42][43][44][45][46][47][48][49][50] The homopolymers 3alkylselenophene (P3AS) 51,52 and 3-alkyltellurophene (P3ATe) 53,54 have also been prepared using the KCTP. We were interested in studying the effects of incorporating two different chalcogenophenes into a single polymer to generate a new class of poly(bichalcogenophene)s. By integrating thiophene, selenophene, and tellurophene units in a single polymer in a controlled sequence, the properties of the polymer could presumably be tailored specically.…”
Section: Introductionmentioning
confidence: 99%